penerapan syirkah melalui akad Musyarakah basmalah Sidogiri Pasuruan - Amirul Taufiqulhakim; Achsania Hendratmi (Universitas Airlangga, 2019)
The purpose of this study was to find out the process of applying the Musyarakah contract carried out by Basmalah Sidogiri in Pasuruan with its partners in opening new branches and investing as new members. This study uses qualitative methods using explanative case study methods. Primary data collection is conducted by interviews and direct observation to informants, they are Head of Marketing Division, Head of Finance Division, Basmalah Partners in Surabaya, and Investors. Secondary data collections are from journals, books, BPS, Web of Basmalah, and other literature.Keywords: Musyarakah Contract, Basmalah, Sidogiri